Kinetics of the complete combustion of dilute propane and methyl ethyl ketone over Cr-doped ZrO2 catalyst - Choudhary, Vasant R.; Deshmukh, G. M. (Chemical Engineering Science, 2005)
The kinetics of the complete combustion of propane and methyl ethyl ketone (MEK) at very low concentration in air (0.45 and 0.4 mol% in air, respectively) over Cr-doped ZrO2 (cubic) catalyst (Cr/Zr = 0.25) at different temperatures (485-673 K) in the kinetic control regime have been investigated. The combustion rate data could be fitted well to both the power law and redox (Mars-Van Krevelen) models. From the power law model, the apparent activation energy for the combustion of propane and MEK has been found to be 16.5 and 13.2 kcal mol(-1), respectively. Among the two models, the redox one, however, gave a better fit to the kinetic data for both the combustion of propane and MEK. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: combustion kinetics; combustion of methyl ethyl ketone; combustion of propane; Cr-doped ZrO2 (cubic) catalyst; methyl ethyl ketone; propane